Новый вид клещей рода Poecilochirus (Mesostigmata, Parasitidae) из Крыма - Винник, E.H. (Вестник зоологии, 1993)
P. doncitus sp. n. is described after 3 deutonymphs found under elytrae of Silpha carinala Ilbst. From closely related species differs by the absence of dark stripe on the sternal shield, expanded setae of the grathsome and II and III coxae. Type material is deposited in the Institute of Zoology, Ukrainian Academy of Sciences (Kiev).